Fitoremediasi Limbah Cair Tahu Menggunakan Tumbuhan Eceng Gondok (Eichhornia crassipes) dan Arang Kayu - Damayanti, Alinda; Binawati, Diah Karunia (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Tofu liquid waste produces toxic compounds that can pollute the environment. Pollution due to tofu liquid waste causes the aquatic environment to become dirty and smelly. Phytoremediation is considered an innovative, economical and relatively safe technology for the environment, because phytoremediation is an effort to use plants to decontaminate waste. Water hyacinth is considered a weed in waters, but has the ability to absorb organic substances, inorganic substances and heavy metals which are pollutants. Wood charcoal can be used as a pollutant absorber in water purification systems. This research aims to improve the quality of tofu liquid waste with a phytoremediation process using water hyacinth plants and wood charcoal with TDS, pH and COD test parameters. This research used 18 experimental tanks with 3 treatments and 6 replications. P1 (100% EG), P2 (75% EG + 25% AK), P3 (50% EG + 50% AK). In this research, the phytoremediation process using water hyacinth plants and wood charcoal was able to improve the quality of tofu liquid waste. Based on the results of the Two Way ANOVA test, it is known that phytoremediation treatment has a significant effect on the test parameters with a significance level of 5%. The results of the phytoremediation study showed TDS levels from 610 mg/L to 589 mg/L; pH from 5.1 to 7.17; and COD from 3000 mg/L to 115.83 mg/L.